Comprehensive experimental and theoretical investigations on the effect of microbubble two-phase flow on the performance of direct-contact membrane distillation. (1st February 2023) - Kim, Yu-Bin; Lee, Ho-Saeng; Gil, Geon-Woo; Ji, Ho; Kim, Young-Deuk
Highlights: MBG-assisted DCMD permeation flux was experimentally and theoretically determined. Optimal MBG configuration and air flow rate were demonstrated by bubble size distribution. Microbubbles in feed stream further enhances heat and mass transfer in DCMD process. Conventional two-phase heat transfer correlations have limitations in predicting permeation flux. Heat transfer correlation considering microbubble size distribution was proposed and verified. Abstract: This study provides a comprehensive and systematic overview of the application of gas-liquid two-phase flow with microbubbles in the feed stream to improve heat and mass transfer in direct-contact membrane distillation (DCMD) processes for seawater desalination. A swirl-flow-type microbubble generator (MBG) was installed at the feed-side inlet of the DCMD module to investigate its effect on transmembrane flux. The maximum improvement in the MBG-assisted DCMD permeation flux was found to be approximately 18% at a lower feed temperature (40 °C) and optimal air flow rate (50 cc/min), and an optimal MBG geometry comprising a swirler, a nozzle tip of diameter 2 mm, and a diffuser at an angle of 30°. The results were observed to be related to the number density of microbubbles less than 100 µm in size, which plays an important role in improving heat and mass transfer in two-phase flow. In addition, the simulation results based on conventional heat transfer correlations of bubbly flow underestimated the experimental results. Therefore, this study also aims to propose and verify a new two-phase flow heat transfer correlation. The proposed correlation considers the effects of bubble size distribution to accurately predict the performance of MBG-assisted DCMD processes.